Expression of the KNOTTED HOMEOBOX Genes in the Cactaceae Cambial Zone Suggests Their Involvement in Wood Development - Reyes-Rivera, Jorge; Rodríguez-Alonso, Gustavo; Petrone, Emilio; Vasco, Alejandra; Vergara-Silva, Francisco; Shishkova, Svetlana; Terrazas, Teresa (Frontiers in Plant Science, 2017)
The vascular cambium is a lateral meristem that produces secondary xylem (i.e., wood) and phloem. Different Cactaceae species develop different types of secondary xylem; however, little is known about the mechanisms underlying wood formation in the Cactaceae. The KNOTTED HOMEOBOX (KNOX) gene family encodes transcription factors that regulate plant development. The role of class I KNOX genes in the regulation of the shoot apical meristem, inflorescence architecture, and secondary growth is established in a few model species, while the functions of class II KNOX genes are less well understood, although the Arabidopsis thaliana class II KNOX protein KNAT7 is known to regulate secondary cell wall biosynthesis. To explore the involvement of the KNOX genes in the enormous variability of wood in Cactaceae, we identified orthologous genes expressed in species with fibrous (Pereskia lychnidiflora and Pilosocereus alensis), nonfibrous (Ariocarpus retusus), and dimorphic (Ferocactus pilosus) wood. Both class I and class II KNOX genes were expressed in the cactus cambial zone, including one or two class I paralogs of KNAT1, as well as one or two class II paralogs of KNAT3-KNAT4-KNAT5. While the KNOX gene SHOOTMERISTEMLESS (STM) and its ortholog ARK1 are expressed during secondary growth in the Arabidopsis and Populus stem, respectively, we did not find STM orthologs in the Cactaceae cambial zone, which suggests possible differences in the vascular cambium genetic regulatory network in these species. Importantly, while two class II KNOX paralogs from the KNAT7 clade were expressed in the cambial zone of A. retusus and F. pilosus, we did not detect KNAT7 ortholog expression in the cambial zone of P. lychnidiflora. Differences in the transcriptional repressor activity of secondary cell wall biosynthesis by the KNAT7 orthologs could therefore explain the differences in wood development in the cactus species.